Comparison of frequency of complications in loop versus divided colostomy in patients with high variety anorectal malformation - Masood Shah; Nabi Bux Napar; Faryal Ilyas Jhammat; Hafiza Shehla Arshad; Mohammed Saleem (EL-Med-Pub, 2020)
Background: The objective of this study was to compare frequency of stoma related complications of loop versus divided sigmoid colostomy for the management of high variety anorectal malformations. Methodology: This RCT was conducted in the department of Pediatrics Surgery Department of the Children's Hospital and the Institute of Child Health Lahore, for the period of one year from 1st May 2016 to 1st June 2017. One hundred and twenty patients (Sixty patients in each group) of anorectal malformation meeting inclusion criteria were taken in this study. Patients were divided into two groups randomly using lottery method; loop sigmoid colostomy in Group-A and divided sigmoid colostomy in Group-B. After surgeries patients were followed weekly up till 8 weeks. Stoma related complications (as per operational definition) were noted. Results: The mean age in group -A and group-B were 3.34 ± 1.12 days and 3.36 ± 0.97 days, respectively. In group - A there were 52(86.67%) male and 8(13.33%) females, and in group-B there were 45(75%) male and 15(25%) female patients. In group-A 22(36.66%) patients had complications [3(5.00%) patients had retraction, 8(13.33%) had prolapse, 4(6.67%) had stoma obstruction, parastomal hernia were seen in 4(6.67%), stoma necrosis were seen in 3 (5.00%)] and in group-B, 16(26.66%) patients had different complications [1(1.67%) patients had retraction, 3(5.00%) had prolapse, 5(8.33%) had stoma obstruction, parastomal hernia were seen in 2(3.3%), stoma necrosis were seen 5(8.33%)]. The complications in group-A were higher when compared to group-B, but (p-value = 0.650) were not significant statistically except for stoma prolapse. Conclusion: Though complication rate in both techniques is not statistically different but frequency of stoma prolapse is more in loop colostomy group. Therefore, divide colostomy should be opted as preferred technique.